Prediction of Benefit from Checkpoint Inhibitors in Mismatch Repair Deficient Metastatic Colorectal Cancer: Role of Tumor Infiltrating Lymphocytes. (22nd January 2020) - Loupakis, Fotios; Depetris, Ilaria; Biason, Paola; Intini, Rossana; Prete, Alessandra Anna; Leone, Francesco; Lombardi, Pasquale; Filippi, Roberto; Spallanzani, Andrea; Cascinu, Stefano; Bonetti, Luca Reggiani; Maddalena, Giulia; et al.
Abstract: Background: Immunotherapy with immune checkpoint inhibitors (ICIs) is highly effective in microsatellite instability–high (MSI‐H) metastatic colorectal cancer (mCRC); however, specific predictive biomarkers are lacking. Patients and Methods: Data and samples from 85 patients with MSI‐H mCRC treated with ICIs were gathered. Tumor infiltrating lymphocytes (TILs) and tumor mutational burden (TMB) were analyzed in an exploratory cohort of "super" responders and "clearly" refractory patients; TILs were then evaluated in the whole cohort of patients. Primary objectives were the correlation between the number of TILs and TMB and their role as biomarkers of ICI efficacy. Main endpoints included response rate (RR), progression‐free survival (PFS), and overall survival (OS). Results: In the exploratory cohort, an increasing number of TILs correlated to higher TMB (Pearson's test, p = .0429). In the whole cohort, median number of TILs was 3.6 in responders compared with 1.8 in nonresponders (Mann‐Whitney test, p = .0448). RR was 70.6% in patients with high number of TILs (TILs‐H) compared with 42.9% in patients with low number of TILs (odds ratio = 3.20, p = .0291). Survival outcomes differed significantly in favor of TILs‐H (PFS: hazard ratio [HR] = 0.42, p = .0278; OS: HR = 0.41, p = .0463). Conclusion: A significant correlation between higher TMB and increased number of TILs was shown. A significantly higher activity and better PFS and OS with ICI in MSI‐H mCRC were reported in cases with high number of TILs, thus supporting further studies of TIL count as predictive biomarker of ICI efficacy. Implications for Practice: Microsatellite instability is the result of mismatch repair protein deficiency, caused by germline mutations or somatic modifications in mismatch repair genes. In metastatic colorectal cancer (mCRC), immunotherapy (with immune checkpoint inhibitors [ICIs]) demonstrated remarkable clinical benefit in microsatellite instability–high (MSI‐H) patients. ICI primary resistance has been observed in approximately 25% of patients with MSI‐H mCRC, underlining the need for predictive biomarkers. In this study, tumor mutational burden (TMB) and tumor infiltrating lymphocyte (TIL) analyses were performed in an exploratory cohort of patients with MSI‐H mCRC treated with ICIs, demonstrating a significant correlation between higher TMB and increased number of TILs. Results also demonstrated a significant correlation between high number of TILs and clinical responses and survival benefit in a large data set of patients with MSI‐H mCRC treated with ICI. TMB and TILs could represent predictive biomarkers of ICI efficacy in MSI‐H mCRC and should be incorporated in future trials testing checkpoint inhibitors in colorectal cancer. Abstract : This article explores the role of tumor mutational burden and number of tumor infiltrating lymphocytes in determining response and outcome of patients with microsatellite high metastatic colorectal cancer treated with immune checkpoint inhibitors.